Evolution of the residual stresses of types I, II, and III of duplex stainless steel during cyclic loading in high and very high cycle fatigue regimes. (January 2021) - Fu, Hongwang; Dönges, Benjamin; Krupp, Ulrich; Pietsch, Ullrich; Fritzen, Claus-Peter; Yun, Xinbing; Christ, Hans-Jürgen
Graphical abstract: Highlights: Residual stresses of the types I, II, and III of a DSS were determined. The type I residual stress can improve the fatigue strength of the DSS in VHCF. Types II and III RSs dominate the formation of microcracks of the DSS in VHCF. Abstract: Residual stresses (RSs) in the very high cycle fatigue regime have to be evaluated, as in some cases they are comparable with the applied stress, affecting the fatigue behaviour. In this work, the evolution of RSs in terms of types I, II, and III was investigated for a duplex stainless steel (DSS) during cyclic loading in high and very high cycle fatigue regimes. The results showed that the type I RS can increase the fatigue strength and prolong the fatigue life remarkably while the types II and III RSs varying in micro-scale dominate the micro-crack initiation mechanism of the DSS.